A large Italian observational multicentre study on vascular ulcers of the lower limbs (Studio Ulcere Vascolari). Issue 1 (12th February 2014) - Apollonio, Alessandro; Antignani, Pier L; Di Salvo, Michelangelo; Failla, Giacomo; Guarnera, Giorgio; Mosti, Giovanni; Ricci, Elia
Abstract: An observational study of 2 years was promoted by the Italian Association for Cutaneous Ulcers (AIUC) in order to monitor the epidemiology of leg ulcers, the trend of healing and the more frequent therapeutic approaches in lower limb ulcers. Fifty‐nine sites in 14 different Italian regions involved in the study, with 1333 enrolled patients (1163 patients fully evaluated and followed up for 9 months). A prevalence of females (62%) was observed with a mean age of 70 years and a high rate of hypertension (62%), diabetes (38%) and obesity (29%). Venous ulcer was most frequent (55%), followed by mixed (25%) and diabetic (8·3%) ulcers. Basically, all patients received a local therapy (LT) (compression and advanced local therapies), while 63% of patients have an associated systemic pharmaceutical treatment. Ulcer healing rates progressively increased throughout the study and despite the type of observational study does not allow conclusions on the treatment, it was observed that the patients receiving additional systemic drugs were associated with a more rapid acceleration of healing rates of ulcers compared to LT alone (3 months: 39·7% versus 29·2%; 6 months: 62·0% versus 47·0%; 9 months: 74·7% versus 63·8%). In particular, the Studio Ulcere Vascolari (SUV) study showed that a combination treatment with sulodexide and compression therapy allows for a greater increase in the healing rates in venous ulcers.